Coping with drought in rice farming in Asia: insights from a cross-country comparative study - Pandey, Sushil; Bhandari, Humnath; Ding, Shijun; Prapertchob, Preeda; Sharan, Ramesh; Naik, Dibakar; Taunk, Sudhir K.; Sastri, Asras (Wiley, 2007)
Drought is a major constraint affecting rice production, especially in rainfed areas of Asia. Despite its importance in rice‐growing areas, the magnitude of economic losses arising from drought, its impact on farm households, and farmers' drought coping mechanisms are poorly understood. This article provides insights into these aspects of drought based on a cross‐country comparative analysis of rainfed rice‐growing areas in southern China, eastern India, and northeast Thailand. The economic cost of drought is found to be substantially higher in eastern India than in the other two countries. Higher probability and greater spatial covariance of drought and less diversified farming systems with rice accounting for a larger share of household income are the main reasons for this higher cost of drought in eastern India. Farmers deploy various coping mechanisms but such mechanisms are largely unable to prevent a reduction in income and consumption, especially in eastern India. As a result, welfare consequences on poor farmers are substantial with a large number of people falling back into poverty during drought years. The overall implications for technology design and for policy improvements for drought mitigation and drought relief are discussed in the light of the empirical findings of the study.